Flirting with the Florida heart doctor - Lynn, Janice (Harlequin medical romance, 2024)
Having escaped a toxic relationship, Dr. Hailey is ready to embrace a sun-filled fresh start in Florida. With a new look and new attitude, Hailey's making a habit of saying yes...even to dinner with oh-so charming colleague Cayden! Despite mending hearts for a living, cardiologist Cayden has been unlucky with his own. Dating disasters have left him wary, but beautiful and vivacious Hailey draws him in. Yet regardless of their deepening connection, she's not looking for something serious. Is Cayden flirting with danger, or could they find the happy-ever-after they both stopped hoping for-together?